Zika Virus Communication Preferences of Pregnant Women: Beyond the Verbal - Mallory Ellingson; Allison Chamberlain (Georgia Southern University, 2017)
Background: Pregnant women are frequently a priority group during public health emergencies, including the current Zika virus outbreak. These women turn to prenatal care providers for health information, but providers may not have the time for discussions with every patient. Knowing alternative ways to communicate key Zika-related information to pregnant women is important. Methods: To determine pregnant women's preferences for obtaining Zika information from their prenatal providers, a 27-item survey was administered to 408 pregnant women at four prenatal care clinics in Atlanta between May 5th, 2016 and June 20th, 2016. The anonymous survey evaluated women's preferences for receiving information about three topics: Zika virus, maternal vaccines and safe medications. Chi-square and Fisher's exact tests were used to determine statistical significance of associations between these topics and selected patient characteristics. Significance was evaluated at α=0.05. Results: Educational brochures (63.8%), e-mails (55.2%) and their provider's practice website (40.2%) were women's most preferred modalities for receiving information about Zika virus beyond verbal communication. Most women (73.2%) use the CDC website as their primary source of information about Zika virus; only 19.2% seek that information on their provider's website. Conclusions: Conveying Zika-related information to pregnant women is essential. As public health practitioners create and refine provider-to-patient communications, they can use these findings to ensure their messages align with how women want to receive information (e.g., brochures, emails, provider websites) and take advantage of existing modalities (e.g. their own websites) that providers may not be fully utilizing. Key words: Zika virus, pregnancy, communication, internet, social media, prenatal care providers